Intervention on Knowledge, Attitude and Practices of Maternal and Child Health among Rural Women of Uttarakhand - Singh, Ritu; Bisht, Niharika (Indian Journal of Extension Education, 2025)
The health of mothers and children is a key indicator of general health in any society. Throughout the world, there is increasing concern and interest in maternal and child health care. Despite that, the morbidity and mortality rates especially in developing countries continue to be alarming. Given the magnitude of these problems and the services available, much improvement has not been witnessed. The present study seeks to assess knowledge, attitude and practices of rural women towards maternal and child health and examined KAP about the process of reproduction, family planning methods, antenatal care, perinatal care, hygiene and nutrition of child. Towards this end, an intervention module was developed and implemented. Pre and post-test were conducted to study the impact of the intervention. The results revealed that during the pretest phase majority of the respondents had moderate knowledge about the signs of pregnancy, importance of first trimester of pregnancy, however gaps were found in knowledge regarding immunization and welfare programmes and services for mothers and young children. A paradigm shift in the knowledge, attitude and practices of rural women towards maternal and child health was observed post intervention. The proportion of women believing in myths like feeding sweetened water or honey to new born, putting oil in baby’s ear decreased post intervention. Inappropriate practices followed pertaining to hygiene and sanitation like non sterilization of feeding bottle before every feed and irregular napkin changes also improved between pre and post intervention.